Timing since deforestation for pastures implementation in the western Amazon: Impacts on stream water biogeochemistry - de Paula, Felipe Rossetti; Brejão, Gabriel Lourenço [UNESP]; Pérez-Mayorga, María Angélica [UNESP]; Casatti, Lilian [UNESP]; de Barros Ferraz, Silvio Frosini; Krusche, Alexandra Montebelo; Krusche, Alex Vladimir (Elsevier, 2025)
Water quality degradation is a global concern and land use changes is one of the main causes of water pollution globally. In the Brazilian Amazon, large-scale deforestation is mostly associated to pasturelands, with strong implications for soils and stream waters biogeochemistry and resulting in environmental degradation. Studies addressing soil biogeochemistry in Amazonian pastures of different ages documented a consistent pattern of elements peaking on the first years after deforestation, followed by a continuous decrease until reach depletion in older, degraded pastures. The same pattern is expected on the adjacent stream water biogeochemistry due to the land-water connection; however, this issue has not being explored. We assessed how timing since deforestation impacts water biogeochemistry in streams of Rondônia State, Brazil, a region that showed a relatively fast colonization process associated to large-scale deforestation for pasture implementation since 1970. Mapping deforestation from 1984 to 2011 and collecting water samples in 2012 for 41 headwater catchments, we (i) compared water biogeochemistry among streams draining undisturbed catchments with primary forests (PRI) and streams draining pasture catchments deforested mostly in a recent (NEW) and in a distant past (OLD); and (ii) related water biogeochemistry with land use intensity (pasture permanency along years), also considering the effect of covariates (soils, forest cover, and catchment area) in our analysis. Our results indicate that pasture implementation altered the concentrations of ions and nutrients in the stream ecosystem, with distinct water quality impacts between newer and older pastures. In general, the longer the area stayed under pasture use, the larger were the alterations in the water biogeochemistry (lower NO3−, DOC, and DOX and higher Ca2+, Mg2+, DIC and COND). Pasture degradation is a widespread process in the Amazon and it is strongly associated to increasing deforestation. Thus, pasture reclamation and intensification is urgently necessary to achieve the long-term productivity and sustainability of Amazonian pasturelands, avoiding new deforestation and environmental degradation. Adopting Best Management Practices (riparian forested buffers) is another action to protect water resources in the region.
Keywords: Environmental management; Land use changes; Nature conservation; Stream ecology; Tropics; Water degradation